How the Arctic Became White: Victorian Explorers and the Erasure of Botany in the Canadian Arctic. : Arcadia: Explorations in Environmental History, Summer 2019, no. 16: How the Arctic Became White: Victorian Explorers and the Erasure of Botany in the Canadian Arctic. - Gismondi, Chris (Rachel Carson Center for Environment and Society, Munich, Germany, 2019)
For many of us “southerners,” we may imagine the Arctic landscape as a desolate frozen landscape. At the historic roots of this perception is the visual culture of Arctic exploration throughout a long nineteenth century which represented the Canadian Arctic as devoid of its diverse flora. Many explorers were interested in natural history and collected botanic specimens; thus this misrepresentation was a deliberate strategy that exaggerated white male Qallunaat explorers’ claims about their accomplishments. Simultaneously, this strategy of representation emphasized European technology and science while downplaying the Indigenous knowledges that were often crucial to the success of expeditions.